The mediating effect of work engagement on the relationship between self-leadership and individual innovation - Gomes, C. (2015)
It has already been demonstrated that individual innovation within the workplace is the fundamental underpinning of high-performance organisations. The aim of this study is to explore the relationship between self-leadership, work engagement and individual innovation. Because innovation manifests itself when individuals feel engaged with their work, we propose that this positive affective motivational state will mediate the relationship between self-leadership skills and individual innovation. To study these relationships, data were collected from a sample of 337 nurses and doctors who work at an integrated health care unit. Our results show a positive relationship between self-leadership, work engagement and individual innovation. Furthermore, the results showed that work engagement had a mediating effect on the relationship between self-leadership and individual innovation. Overall, this research will contribute towards gaining more insights into the role that self-leadership and work engagement play in individual innovation. In addition, it will provide insights into new interventions that promote the development of innovation at work.